Quantifying oxidation level based on the colour of SS316L powder - Lau, Kelly Jing Xuan (Nanyang Technological University, 2021)
Selective Laser Melting (SLM) is a popular 3D printing method for metallic powders. It is capable of printing parts layer by layer while keeping most of the powders unused which can be used again. However, due to laser spatter, heat, and atmospheric condition of the chamber, oxidation of the metallic powder can be observed. This has the potential to affect the flowability of powder, powder layer stability and the built parts. The oxidised powder can have different colours due to the thickness of the oxide layer termed as thin-film interference. Therefore, based on the colours, the oxidation level of powders can be estimated and determined and if the powders would be suitable for use in subsequence builds. To achieve this, powders were oxidised at different temperatures for different colours, SEM-EDX was used to compare the oxidation level of different coloured powders, a custom-made platform, and MatLab Code were used to analyse the powder layer. Upon analysis, it was found that the code and platform can estimate the number of coloured powders and total number of powder particles. The values were used to estimate the oxidation level of each sample as a whole and the individual colours. All in all, the methods used were able to provide a gist of the powder condition in terms of oxidation level which can determine the suitability of the metallic powder to be reused.